Descripción del funcionamiento del Banco de Alimentos Perú - Kamichi Miyashiro, Manuel José (2023)
Around a third of food is lost and wasted in the world each year, while close to 650 million people suffered from malnutrition before the pandemic. In Peru, 12.8 million tons of food end up being wasted every year. For that reason the food banks appeared, whose purpose is to deliver food to people in need thanks to the recovery of groceries that were going to be lost or wasted. The present research describes the operation of the Food Bank of Peru in its process of recovery and delivery food. Among the results found, the efficiency in the delivery of food stands out, thus saving resources, thanks to the application of cross docking, which allows to the organization to carry out their functions without the need of an own warehouse.